The Intersection of Public Health and Infection Control: An Integrated Review of Emerging Threats, Prevention Strategies, and Policy Responses in Global Health Systems - Ibrahim Mohammed Nasser Khubrani; Sultan Abdullah Mohammed Alshehri; Khalid Ali Ahmed Mathwi; Ahmed Ali Mofareh Algharamah; ‎‏Teef Salem Al-Anzi; ‎‏Mohammed Hassan Asiri; Thamer Mohammed Hamoud Halawani (International Journal of Medical Toxicology and Legal Medicine, 2025)
The intersection of public health and infection control has become increasingly critical in the face of emerging global health threats such as pandemics, antimicrobial resistance, and healthcare-associated infections. This integrated review examines the evolving landscape of infection control within public health systems, focusing on the threats posed by infectious diseases, the effectiveness of prevention strategies, and policy responses at both national and international levels. Through a systematic analysis of recent literature, global reports, and case studies, the review highlights how coordinated approaches—combining surveillance, vaccination, health education, and technological innovation—can mitigate the spread of infectious diseases. The study also explores the role of international frameworks such as the International Health Regulations and the Global Health Security Agenda in reinforcing infection control capacities worldwide. Policy gaps, particularly in low- and middle-income countries, are identified as persistent barriers to effective infection control. The review concludes by recommending integrated policy frameworks, capacity building, and cross-sectoral collaborations to strengthen global health systems. Ultimately, the synthesis underscores the necessity of embedding robust infection control within public health policies to enhance resilience against current and future health crises.